2005
DOI: 10.1111/j.1745-9133.2005.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Oriented Policing in Practice*

Abstract: Research Summary: Interviews and surveys were used to measure the extent of problem‐oriented policing (POP) by individual police officers in the San Diego Police Department. Officers tended to engage in small‐scale problem solving with little formal analysis or assessment. Responses generally included enforcement plus one or two more collaborative or nontraditional initiatives. Policy Implications: Despite 15 years of national promotion and a concerted effort at implementation within the San Diego Police Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 6 publications
6
89
0
Order By: Relevance
“…Research on the dosage and fidelity of its actual implementation is rare. This study augments findings from research by Cordner and Biebel (2005) on the implementation of POP in San Diego. Both studies examine implementation issues in agencies regarded as leaders in the POP movement.…”
Section: A Brief History Of Problem-oriented Policing In Colorado Sprsupporting
confidence: 73%
“…Research on the dosage and fidelity of its actual implementation is rare. This study augments findings from research by Cordner and Biebel (2005) on the implementation of POP in San Diego. Both studies examine implementation issues in agencies regarded as leaders in the POP movement.…”
Section: A Brief History Of Problem-oriented Policing In Colorado Sprsupporting
confidence: 73%
“…In contrast, we found in our focus groups that 503 National survey of law enforcement agencies higher-level personnel use long-term crime analysis more routinely, as they require analysis that looks at issues in the longer term (Taylor and Boba, 2011). The stratification of crime analysis by rank can be inferred from a study of ten years of problem solving in San Diego, CA that found that line-level patrol officers tend to look at problems with a very narrow focus (e.g., several calls for service at one address), and therefore do not require formal crime analysis products that are relevant for larger long-term problems (Cordner and Biebel, 2005). Consequently, to integrate crime analysis into policing, particularly patrol work, the literature points to areas of concern related to the types of crime analysis results that are provided to particular personnel and the expectations for how crime analysis is to be used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, to this date, there has been no national survey on the explicit use of crime analysis for crime reduction activities in patrol to determine agencies' use and integration of crime analysis. Studies that have been done have either looked at one agency (Cope, 2004;Cordner and Biebel, 2005) or have focussed on the crime analyst's perspective (O'Shea and Nicholls, 2003). Therefore, this paper presents a series of results from a national survey of police agencies on which future research and implementation of crime analysis can benefit from learning about the identified characteristics of current efforts at integrating crime analysis into the patrol function.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experience with POP teaches us that its practice is not easily achieved (see Capowich et al 1994;Cordner and Biebel 2005; Police Executive Research Forum 2000; Sampson and Scott 2000). The popular SARA model of the POP processScanning, Analysis, Response, and Assessment-makes analysis central to the practice of POP (Eck and Spelman 1987;see also Tilley 2003); analysis, as the SARA model highlights, is the bridge from problem identification to the formulation of possible solutions.…”
Section: Community Policingmentioning
confidence: 99%